Glomerulocystic Kidney Disease and End-stage Renal Disease in a Child: A Rare Case Report and Literature Review: Glomerulocystic Kidney Disease - Sharmim, Shanjida; Huque, Syed Saimul; Uddin, Golam Muin; Begum, Afroza; Akbar, Romana; Hossain, Delwar (Journal of Pediatric Nephrology, 2024)
Glomerulocystic kidney disease (GCKD) is characterized by cystic dilatation of the Bowman’s capsule and adjacent tubules. It is a rare form of cystic kidney disease and can occur at any age. Sometimes GCKD may not be differentiated from other cystic kidney diseases. It usually presents with renal failure. Here, we reported a case of a four-year-old girl presented with end-stage renal disease who had glomerulocystic kidney disease in renal histopathology.